2020
DOI: 10.1177/1076029620935206
|View full text |Cite
|
Sign up to set email alerts
|

PROC Promoter Single Nucleotide Polymorphisms Associated With Low Protein C Activity But Not Increased Risk of Thromboembolism in Pediatric Population

Abstract: Protein C (PC) deficiency, caused by mutations of the PROC gene, is a common inherited risk factor of thromboembolism (TE) among Thai people. This study aimed to investigate the association of 3 single nucleotide polymorphisms (SNPs; −1654 C/T, −1641 A/G, −1461A/T) at the PROC promoter region with PC activity and the risk of developing TE. A total of 216 patient s with TE, diagnosed at aged 0 to 20 years, and 102 healthy adults were enrolled. The SNPs were identified by Sanger sequencing. Protein C ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Rare genetic polymorphisms in the human PC can cause PC deficiency states due to reduced secretion or synthesis of PC (Type I) or changed PC structure (Type II) [11]. On the other hand, common genetic polymorphisms have also been suggested to be associated with relative PC deficiency and with altered outcomes in disorders such as pulmonary embolism, venous thrombosis, cardiovascular disease, stroke, sepsis, and systemic meningococcemia [12][13][14]. Moreover, previous studies have demonstrated that the genetic variants of human PC contribute not only to diseases and disorders but also to the inter-individual variability in dose requirements for anticoagulant drugs such as warfarin.…”
Section: Introductionmentioning
confidence: 99%
“…Rare genetic polymorphisms in the human PC can cause PC deficiency states due to reduced secretion or synthesis of PC (Type I) or changed PC structure (Type II) [11]. On the other hand, common genetic polymorphisms have also been suggested to be associated with relative PC deficiency and with altered outcomes in disorders such as pulmonary embolism, venous thrombosis, cardiovascular disease, stroke, sepsis, and systemic meningococcemia [12][13][14]. Moreover, previous studies have demonstrated that the genetic variants of human PC contribute not only to diseases and disorders but also to the inter-individual variability in dose requirements for anticoagulant drugs such as warfarin.…”
Section: Introductionmentioning
confidence: 99%